THE IMPLEMENTATION OF “GERINTING” AS A SIMULTANEOUS INTERVENTION TO PREVENT STUNTING IN MOJOKERTO REGENCY - Yani, Lasiyati Yuswo; Yulianti, Indra (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Strategies for solving the stunting problem so far are still limited to curative and rehabilitative targets for targets who have been diagnosed with stunting. A problem strategy is needed that focuses on promotive and preventive efforts targeting the community (community) so that the chain of stunting can be broken. The aim of this research is to determine the implementation of the Gerinting movement in Kab. Mojokerto. The design of this research is a quasi-experimental one group pretest posttest design. The research subjects were determined using purposive sampling, namely posyandu at UPT. Jetis Health Center. Data collection uses a questionnaire. The results of the normality test showed that the data was not normally distributed. Hypothesis testing used the Wilcoxon test. The results showed that there was an increase in the mean knowledge score of mothers before the Gerinting movement was 32.80 (SD=9.768), after the Gerinting movement the mean knowledge score was 87.10 (SD=5.677) and the mean action score of mothers before mentoring was 25.83 (SD = 19.122), after providing assistance in the form of counseling, demonstrations and practicums to cadres, the average action score increased to 79.17 (SD = 9.476). In the statistical test results, there was a significant difference before and after the intervention was given with a value of 0.000, (p<0.05). This shows that there is an influence of the Gerinting movement on mothers' knowledge and actions regarding stunting.